Conference on Champa 2007 (American Journal of Islam and Society, 2007)
This first-ever conference convened by the Champa peoples, of whom theCham (both Muslim and non-Muslim) are an important component, focusedon the “Sociocultural Issues of Champa 175 Years after Its Disappearance(1832-2007).” Held on 7-8 July 2007, in San Jose, CA, it was opened byChuck Reed (mayor, San Jose), Musa Porome (chairman, Organizing Committee),Ahmad Yahya (Member of Parliament, Cambodia; founder, RadioSapCham [Voice of the Cham]), and R. Obleo (a representative of theChampa people of the Central Highlands, Vietnam, now living in America).Session One, “Language and Culture,” moderated by Mohammad ZainBin Musa (University Kebangsaan Malaysia), began with Marc Brunelle(University of Ottawa, Canada), who spoke on “Diglossia, Bilingualism,and Literacy: Can Eastern Cham Be Revitalized?” Brunelle, a fluent Chamand Vietnamese speaker, touched upon a core problem; the Cham languagehas not developed enough to accommodate modernity. Thus, the easternCham are generally bilingual, the formal language is limited to importantevents, the spoken language contains many Vietnamese words, regional pronunciationshave appeared, Cham-language written literature is very rare,and the community (traditionally) has opposed the script’s romanization. Hesees two choices to ensure its survival: romanize or simplify the script.David G. Sox (United States Coast Guard Pacific Command, Oakland,CA) presented “Toward a Book/CD-ROM of the Culture and Customs ofAncient Champa and Modern Champa Peoples.” He is seeking the community’sactive participation in documenting Champa’s geography, prehistory ...